Reversible logic circuits made of DNA. - Genot, A; Bath, J; Turberfield, A (American Chemical Society, 2011)
We report reversible logic circuits made of DNA. The circuits are based on an AND gate that is designed to be thermodynamically and kinetically reversible and to respond nonlinearly to the concentrations of its input molecules. The circuits continuously recompute their outputs, allowing them to respond to changing inputs. They are robust to imperfections in their inputs.